A systematic analysis of China's noncommunicable disease policies: policy themes, policy instruments, and policy effectiveness from 2009 to 2025 - Dong, Defeng; Huang, Haojun; Zhou, Aitong; Dong, Chen (Frontiers in Public Health, 2025)
BackgroundNoncommunicable diseases (NCDs) have become a leading threat to life and health. China is facing a more severe challenge from NCDs than ever before, which not only places enormous pressure on the public health system but also significantly hinders economic development and the achievement of sustainable development goals.ObjectiveScientifically sound policies can provide a supportive environment for the prevention and control of NCDs. Therefore, this study aims to identify the strengths and weaknesses of current policies through a multidimensional analysis of policy texts, and to propose corresponding policy recommendations. The goal is to enhance the government's capacity and effectiveness in NCD governance, improve the health level of the entire society, and provide policy insights for China and other countries suffering from NCD burdens.MethodsThis study adopts the Latent Dirichlet Allocation (LDA) topic model, content analysis method, and the Policy Modeling Consistency (PMC) model to conduct a multidimensional evaluation of 50 NCD-related policy documents issued by the Chinese government from 2009 to 2025, focusing on three dimensions: policy themes, policy instruments, and policy effectiveness.Results(1) LDA analysis identified six key policy themes: primary healthcare, health promotion, health equity, healthcare reform and regulation, NCD prevention and control, and public health governance. (2) There was a clear structural imbalance in the use of the three types of policy instruments: supply-type (49.1%), environment-type (36.4%), and demand-type (14.4%). (3) The PMC model was applied to 9 representative policies. Among these, 4 were rated “excellent” and 5 “acceptable,” with an average PMC score of 6.19, indicating moderate internal consistency and scientific design, yet with considerable variance in quality across policies.ConclusionChina's NCD policy framework shows generally sound structure and intent. However, imbalances in tool application, limited demand-side engagement, and insufficient cross-sectoral coordination remain challenges. Enhancing interdisciplinary integration, strengthening incentives, and promoting stakeholder collaboration are essential for optimizing NCD governance.